ANALISIS KEBUTUHAN SISTEM INFORMASI PELANGGARAN KELEMBAGAAN PERGURUAN TINGGI: STUDI KASUS DIREKTORAT JENDERAL KELEMBAGAAN IPTEK DAN DIKTI - Suhandana, Ariawan Andi; Mursanto, Petrus (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Directorate General of Institutional Affairs of Science, Technology and Higher Education in performing tasks and institutional functions requires the availability of data quickly and accurately. Along with the passage of time, the need for information systems of university data management is very necessary especially the data of colleges in violation. Currently, the management is manually stored into excel files which of course have a lot of limitations. This practice resulted in problems in the supervision of the process as well as the problems at the college in violation. To overcome these problems, it is required the design of information systems for problematic colleges that can meet existing business processes. This research used the design of requirements information system that meets the existing processing needs. This design employs the Rational Unified Process method, where the design follows the workflow requirements and is done iteratively as much as 3 iterations. The results of the study are the Requirement Artefact Set document that elaborates in detail the needs of the problematic college information system.